2016
DOI: 10.1177/0003319716646932
|View full text |Cite
|
Sign up to set email alerts
|

Admission Endocan Level may be a Useful Predictor for In-Hospital Mortality and Coronary Severity Index in Patients With ST-Segment Elevation Myocardial Infarction

Abstract: We assessed the prognostic role of serum endocan level in patients with ST-segment elevation myocardial infarction (STEMI) and compared the results with a normal coronary angiography group. A total of 133 patients were included in the study (88 patients with STEMI and 45 patients with normal coronary arteries). The SYNTAX score was determined based on the baseline coronary angiogram. Multivariate logistic regression analysis indicated that endocan independently correlated with the presence of STEMI. Moreover, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(48 citation statements)
references
References 27 publications
1
38
0
5
Order By: Relevance
“…Previous studies have shown the association between the endocan levels and CAD, AMI, newly diagnosed hypertension, and coronary ectasia (9, 10, 31, 32). Kundi et al (10) reported that the admission of high endocan levels is an independent predictor of in-hospital mortality and an increased SYNTAX score in patients with STEMI. Xiong et al (33) investigated the relationship between endocan levels and the presence and severity of CAD in patients with hypertension, and they found an independent correlation between endocan levels and the presence and severity of CAD.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown the association between the endocan levels and CAD, AMI, newly diagnosed hypertension, and coronary ectasia (9, 10, 31, 32). Kundi et al (10) reported that the admission of high endocan levels is an independent predictor of in-hospital mortality and an increased SYNTAX score in patients with STEMI. Xiong et al (33) investigated the relationship between endocan levels and the presence and severity of CAD in patients with hypertension, and they found an independent correlation between endocan levels and the presence and severity of CAD.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies examined the association of endocan with heart disease. [13,26] In a study of 164 patients, Wang et al [27] reported that serum levels of endocan were correlated with the presence and severity of coronary artery disease. Balta et al [13] reported that vascular inflammation played an important role in the pathophysiology of hypertension and that the increased level of endocan may be indicative of untreated hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…Similar studies reported that endocan can be used as a biomarker in the diagnosis and follow-up of cardiovascular diseases. [13,26] They also suggested that endocan induced endothelial activation or dysfunction in endothelium-derived diseases and that it may serve as a biomarker of inflammation in diseases of vascular origin. [13][14][15] Although many studies concluded that an increase in the serum level of endocan was a sign of a worsening disease, there is discord in the literature on this topic.…”
Section: Discussionmentioning
confidence: 99%
“…Endocan was increased by many inflammatory diseases and used as a biomarker for ongoing vascular inflammation and endothelial dysfunction. Increased serum endocan levels were observed in various clinical settings characterized by endothelial dysfunction such as hypertension (21), obstructive coronary artery disease (22), acute coronary syndrome (9,23), and diabetes mellitus (24,25). In the present study, serum endocan level was analyzed in the case of lead exposure, and endothelial dysfunction as main link between lead exposure and diastolic dysfunction has been evaluated by serum endocan level for the first time.…”
Section: Characteristicsmentioning
confidence: 90%